Hadith #587 - Sahih Muslim - Kuraib (Sahih Muslim)
I heard it from Maimuna, the wife of the Messenger of Allah (way peace be upon him): The Messenger of Allah (ﷺ) used to lie with me when I menstruated, and there was a cloth between me and him.
Grade: Sahih

Hadith #1288 - Sahih Muslim - Kuraib (Sahih Muslim)
You observe with us the prayer. He commanded Bilal, and he uttered the call to prayer in the darkness of night preceding daybreak and he said the morning prayer till dawn had appeared. He then commanded him (Bilal) to call for the noon prayer when the sun had declined from the zenith. He then commanded him (Bilal) to call for the afternoon prayer when the sun was high. He then commanded him for the evening prayer when the sun had set. He then commanded him for the night prayer when the twilight
Grade: Sahih

Hadith #1681 - Sahih Muslim - Kuraib (Sahih Muslim)
I also stood up and did the same, as the Messenger of Allah (ﷺ) had done, and then went to him and stood by his side. The Messenger of Allah (ﷺ) placed his right hand upon my head and took hold of my right ear and twisted it, and then observed a pair of rak`ahs, again a pair of rak`ahs, again a pair of rak`ahs, again a pair of rak`ahs, again a pair of rak`ahs, again a pair of rak`ahs, and then observed Witr and then lay down till the Mu’adhdhin came to him. He (the Holy Prophet) then stood
Grade: Sahih

Hadith #1689 - Sahih Muslim - Kuraib (Sahih Muslim)
The Messenger of Allah (ﷺ) stood near the water-skin and poured water out of it and performed ablution in which he neither used excess of water nor too little of it, and the rest of the hadith is the same, and in this mention is also made (of the fact) that on that night the Messenger of Allah (ﷺ) made supplication before Allah in nineteen words. Kuraib reported: I remember twelve words out of these, but have forgotten the rest. The Messenger of Allah (ﷺ) said: “Place light in my heart,
Grade: Sahih

Hadith #1743 - Sahih Muslim - Kuraib (Sahih Muslim)
‘Abdullah b. Qais or al-Ash’ari has been gifted with a sweet melodious voice out of the voices of the family of David.
Grade: Sahih

Hadith #1825 - Sahih Muslim - Kuraib (Sahih Muslim)
I along with ‘Umar b. al-Khattab dissuaded people to do so (to observe two rak’ahs of prayer). Kuraib said: I went to her (‘A’isha) and conveyed to her the message with which I was sent. She said: (Better) ask Umm Salama. So I went to them (those who had sent him to Hadrat ‘A’isha) and informed them about what she had said. They sent me back to Umm Salama with that with which I was sent to ‘A’isha. Umm Salama said: I beard the Messenger of Allah (ﷺ) prohibiting them, and then a
Grade: Sahih

Hadith #2412 - Sahih Muslim - Kuraib (Sahih Muslim)
When did you see it? I said: We saw it on the night of Friday. He said: (Did) you see it yourself? I said: Yes, and the people also saw it and they fasted and Mu’awiya also fasted, whereupon he said: But we saw it on Saturday night. So we will continue to fast till we complete thirty (fasts) or we see it (the new moon of Shawwal). I said: Is the sighting of the moon by Mu’awiya not valid for you? He said: No; this is how the Messenger of Allah (ﷺ) has commanded us. Yahya b. Yahya was in do
Grade: Sahih

Hadith #2585 - Sahih Muslim - Kuraib (Sahih Muslim)
” Fasting for one month.”
Grade: Sahih

Hadith #2936 - Sahih Muslim - Kuraib (Sahih Muslim)
” They felt jealous of him. but said: The people of Mecca, were jealous people.”
Grade: Sahih

Hadith #2978 - Sahih Muslim - Kuraib (Sahih Muslim)
Allah’s Messenger (ﷺ) proceeded from ‘Arafa, and as he approached the creek of a hill, he got down (from his camel) and urinated, and then performed a light ablution. I said to him: Prayer, whereupon he said: The prayer awaits you (at Muzdalifa). So he rode again, and as he came to Muzdalifa, he got down and performed ablution well. Then Iqima was pronounced for prayer, and he ‘observed the sunset prayer. Then every person made his camel kneel down there, and then Iqama was pronounced fo
Grade: Sahih

Hadith #2981 - Sahih Muslim - Kuraib (Sahih Muslim)
We came to a valley where people generally halted their (camels) for the sunset prayer. Allah’s Messenger (ﷺ) halted his camel and urinated (and he did not say that he had poured water). He then called for water and performed light ablution. I said: Messenger of Allah, the prayer! Thereupon he said: Prayer awaits you (at Muzdalifa). and he rode on until we came to Muzdalifa. Then he offered the sunset prayer. and the people halted their camels at their places, and did not untie them until Iq
Grade: Sahih

Hadith #3133 - Sahih Muslim - Kuraib (Sahih Muslim)
A woman lifted a child and said: Messenger of Allah, would he be credited with Hajj? He said: Yes. and for you there would be a reward.
Grade: Sahih

Hadith #3910 - Sahih Muslim - Kuraib (Sahih Muslim)
The best treatment which you get is cupping. or aloeswood and do not torture your children by pressing their uvula.
Grade: Sahih

Hadith #5745 - Sahih Muslim - Kuraib (Sahih Muslim)
He who played Nardashir (a game similar to backgammon) is like one who dyed his hand with the flesh and blood of swine.
Grade: Sahih

Hadith #5915 - Sahih Muslim - Kuraib (Sahih Muslim)
I said to Abu Tufail: Did you see Allah’s Messenger (ﷺ)? He said: Yes, he had a white handsome face. Muslim b. Hajjaj said: Abu Tufail who died in 100 Hijra was the last of the Companions of Allah’s Messenger (ﷺ).
Grade: Sahih